Efeito de diferentes faixas de amplitude de conhecimento de resultados na aquisição de habilidades motoras - Alessandra Aguilar Coca Ugrinowitsch (2008)
The bandwidth KR is an important factor in the motor skills acquisition.In general, it has been asked which bandwidth KR is the most effective in the motorskills acquisition, whether there is some difference between the absence ofquantitative information with and without meaning to the learner. There are fewstudies that investigated this form of feedback effect and overall the results are quiteinconclusives. The present study had the goal of testing if motor skill acquisitionshould be facilitated with differents bandwidth KR and also if absence of meaningquantitative information helps this process of skill acquisition in a different way, whencompared to the absence of no meaning quantitative information. It was used apositioning motor task of typing the numeric computer keyboard with the time target of900 ms. Eigth groups were formed: 100% bandwidth (G100) that does not receivedquantitative KR; 0% bandwidth (G0) that received quantitative KR in every trial; thinbandwidth that received quantitative KR when the error was higher than 5% (G5);intermediate bandwidth that received quantitative KR when the error was higher than10% (G10); wide bandwidth that received quantitative KR when the error was higherthan 15% (G15); three more yoked groups for the thin bandwidth KR (GPE)intermediate (GPI) and wide (GPA) that received KR in the same trials that bandwidthgroups, but they do not know the absence of quantitative information meaning. Eachsubject practiced 50 trials during acquisition phase and 10 trials in transfer test, whenno one group had augmented KR and the time target increased to 1100 ms. In the allbandwidth groups comparition, G100 had the worst performance during transfer testshowing the quantitative KR importance for learning but did not show the bandwidthviiiKR effect. In the each bandwidth group analyzis with your respective yoked groupthere was no difference between them, neither in the precision nor in the consistency,independently of te bandwidth analyzed. It is possible that the used time targets inboth phases of the experiment were equidistants and very close from one referencetime for all the subjects (one second). The results were unconclusives in relation tothe bandwidth KR theoreticals predictions and show the necessity of more studies inthe future.